Sentendence
New member
- Joined
- May 29, 2013
- Messages
- 7
\(\displaystyle e^{\pi}=(e^{i\pi})^{-i}=(-1)^{-i}=\frac{1}{(-1)^{i}}\)
Implies that
\(\displaystyle e^{\pi} = \frac{1}{(-1)^{i}}\)
\(\displaystyle e^{\pi}(-1)^{i}=1\)
\(\displaystyle e^{\pi}(-1)^{i}=(-1)(-1)\)
\(\displaystyle e^{\pi}(-1)^{i}=e^{i\pi}(-1)\)
\(\displaystyle \ln (e^{\pi}(-1)^{i})=\ln(e^{i\pi}(-1))\)
\(\displaystyle \pi\ln(e)+i\ln(-1)=i\pi \ln(e)+\ln(-1)\)
\(\displaystyle \pi\ln(e)[1-i]=\ln(-1)[1-i]\)
\(\displaystyle \pi\ln(e)[1-i]-\ln(-1)[1-i]=0\)
\(\displaystyle [1-i][\pi\ln(e)-\ln(-1)]=0\)
\(\displaystyle [1-i][\pi-i\pi]=0\\\)
\(\displaystyle \pi[1-i][1-i]=0\\\)
Implies that i = 1
P.S How do you change this to display LaTeX code ?
Implies that
\(\displaystyle e^{\pi} = \frac{1}{(-1)^{i}}\)
\(\displaystyle e^{\pi}(-1)^{i}=1\)
\(\displaystyle e^{\pi}(-1)^{i}=(-1)(-1)\)
\(\displaystyle e^{\pi}(-1)^{i}=e^{i\pi}(-1)\)
\(\displaystyle \ln (e^{\pi}(-1)^{i})=\ln(e^{i\pi}(-1))\)
\(\displaystyle \pi\ln(e)+i\ln(-1)=i\pi \ln(e)+\ln(-1)\)
\(\displaystyle \pi\ln(e)[1-i]=\ln(-1)[1-i]\)
\(\displaystyle \pi\ln(e)[1-i]-\ln(-1)[1-i]=0\)
\(\displaystyle [1-i][\pi\ln(e)-\ln(-1)]=0\)
\(\displaystyle [1-i][\pi-i\pi]=0\\\)
\(\displaystyle \pi[1-i][1-i]=0\\\)
Implies that i = 1
P.S How do you change this to display LaTeX code ?
Last edited by a moderator: